2007
DOI: 10.1093/jxb/erm219
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics, pigment composition, and organization of thylakoid membranes in iron-deficient spinach leaves

Abstract: The changes induced in the photosynthetic apparatus of spinach (Spinacia oleracea L.) seedlings exposed to iron deficiency shortly after germination were characterized with two proteomic approaches coupled with chlorophyll and xanthophyll analysis and in vivo measurements of photosynthesis. During the first 10 d of iron deficiency the concentrations of chlorophyll b and violaxanthin were greatly reduced, but all xanthophylls recovered after 13-17 d of iron deficiency, when both chlorophylls were negatively aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
84
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 77 publications
13
84
3
Order By: Relevance
“…It is of interest to place our findings in the context of studies that have reported on the general effects of Fe deficiency on chlorophyll synthesis and photosynthesis that have been well documented in the literature (Spiller and Terry, 1980;Andaluz et al, 2006;Nishio and Terry, 1983;Nishio et al, 1985;Sharma, 2007;Timperio et al, 2007;Laganowski et al, 2009;Msilini et al, 2011;Ciaffi et al, 2013;Paolacci et al, 2014;Rodríguez-Celma et al, 2013). Some studies on Fe depletion in plants reported that PSI was the major target of Fe deficiency (Nishio et al, 1985;Timperio et al, 2007), whereas we saw a major effect on the cytochromeb 6 f complex and less on PSI.…”
Section: Fe Sparing In Chloroplasts Targets Abundant Fe Proteinssupporting
confidence: 61%
See 1 more Smart Citation
“…It is of interest to place our findings in the context of studies that have reported on the general effects of Fe deficiency on chlorophyll synthesis and photosynthesis that have been well documented in the literature (Spiller and Terry, 1980;Andaluz et al, 2006;Nishio and Terry, 1983;Nishio et al, 1985;Sharma, 2007;Timperio et al, 2007;Laganowski et al, 2009;Msilini et al, 2011;Ciaffi et al, 2013;Paolacci et al, 2014;Rodríguez-Celma et al, 2013). Some studies on Fe depletion in plants reported that PSI was the major target of Fe deficiency (Nishio et al, 1985;Timperio et al, 2007), whereas we saw a major effect on the cytochromeb 6 f complex and less on PSI.…”
Section: Fe Sparing In Chloroplasts Targets Abundant Fe Proteinssupporting
confidence: 61%
“…Some studies on Fe depletion in plants reported that PSI was the major target of Fe deficiency (Nishio et al, 1985;Timperio et al, 2007), whereas we saw a major effect on the cytochromeb 6 f complex and less on PSI. The severity of the applied Fe deficiency, differences in light conditions, and the use of different species may all help determine if PSI or the cytochrome-b 6 f complex is more affected.…”
Section: Fe Sparing In Chloroplasts Targets Abundant Fe Proteinscontrasting
confidence: 48%
“…For example, Fe resupply leads to increases in Chl concentration and photosynthetic rate [15,16] and decreases in the concentration of organic acids [4,17]. Additionally, the reduction of the carboxylate concentration in xylem sap and in leaf apoplast was also reported in sugar beet [18] and fruit trees [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review paper, [1] stated that studies involving the responses of Fe-deficient plants resupplied with Fe are still scarce and may provide crucial [15] information for the optimization of the Fe-fertilization strategies. The aims of the present study were to characterize the changes induced by Fe depletion on the Chl content, root FC-R and mineral composition of roots and leaves and to compare two different ways to resupply Fe: by foliar or root fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…thaliana leaves were washed with cold water and used for extraction of thylakoid membranes as described by Timperio et al [9] and processed as described by D' Amici et al [10]. BN-SDS-PAGE, image analysis, tryptic digestion of proteins, peptide sequencing and identification was done as described previously [6].…”
Section: Thylakoid Isolation and Blue-native Pagementioning
confidence: 99%